2003
DOI: 10.1073/pnas.1533326100
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an RNA·DNA hybrid reveals intermolecular intercalation: Dimer formation by base-pair swapping

Abstract: An intermolecular intercalation of base pairs was found at the CA step in the I222 crystal structure of the RNA⅐DNA hybrid, r(CAAAGAAAAG)⅐d(CTTTTCTTTG), which contains two-thirds of the polypurine tract sequence of HIV-1 with a substitution of cytosine for the initial adenine. This sequence crystallized in both P2 12121 and I222 space groups, with an rms difference of only 0.63 Å between residues 3 to 18 of the two forms. P2 12121 and I222 helices are both A-like, but intercalation occurs only in the I222 crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…It is known that anisotropy is related to the transfer angle between donor emission and acceptor absorption as (assuming that the transfer time is much smaller than the time needed for reorientation of dipole moments due to helix twisting) as Simple calculations show that angle u should be close to *45°. In support of our conjecture calculations of the angle between transition dipole moments of the Cy3 and Cy5 fluorophores stacked to the ends of DNA/RNA duplex show that this is close to *500°-508°(sum of Cy3 and Cy5 rotations relative to the end base pairs is equal to 62°, Iqbal et al 2008a, helical twist is equal either 31.3°or 31.9°, Han et al 2003) or, equivalently, to *31°-40°. We note that these data corroborate the assumption about stacking of Cy3 and Cy5 fluorophores to the ends of DNA/ RNA helix which are not impaired by the nature of the linkers used.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is known that anisotropy is related to the transfer angle between donor emission and acceptor absorption as (assuming that the transfer time is much smaller than the time needed for reorientation of dipole moments due to helix twisting) as Simple calculations show that angle u should be close to *45°. In support of our conjecture calculations of the angle between transition dipole moments of the Cy3 and Cy5 fluorophores stacked to the ends of DNA/RNA duplex show that this is close to *500°-508°(sum of Cy3 and Cy5 rotations relative to the end base pairs is equal to 62°, Iqbal et al 2008a, helical twist is equal either 31.3°or 31.9°, Han et al 2003) or, equivalently, to *31°-40°. We note that these data corroborate the assumption about stacking of Cy3 and Cy5 fluorophores to the ends of DNA/ RNA helix which are not impaired by the nature of the linkers used.…”
Section: Discussionsupporting
confidence: 72%
“…where r is the inter-dye distance, N is the number of base pairs, H rise is the rise of DNA/RNA helix (H rise & 3.0 or 2.7 Å (Han et al 2003)) and u is the polar angle between donor and acceptor orientations. L 0 should be considered as the sum of the Cy3 and Cy5 rises (8 Å ; Iqbal et al 2008a) L D and L A can be considered as off-centre distances for donor and acceptor, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The intercalation does not increase base overlap for the base tetrad (Fig. 4), which is different from the base pair swapping in duplex structure (9). The backbone torsion angles of the U1-G2 step of the eight strands are shown in Table 1.…”
Section: Resultsmentioning
confidence: 87%
“…NMR study indicated that cytosine-rich RNA sequences also could form the i-motif in solution, even though they are less stable than their DNA counterparts (8). Recently, intercalation of G⅐C and A⅐T base pairs at the junction of two RNA⅐DNA hybrid duplexes formed a fragment of quadruplex (9).…”
mentioning
confidence: 99%
“…Precisely how the preferred nucleotides facilitate RNase H cleavage is unknown, but it has been proposed that the structures associated with some hybrid sequences might affect cleavage specificity (35). Several features influenced by sequence are the base composition, the trajectory of the helical axis, and the width of the major and minor grooves (35,47,48). Although it is possible that the preferred nucleotides flanking a cleavage site reflect interactions in the DNA strand instead of or in addition to the RNA strand, the co-crystal structure of HIV-1 reverse transcriptase and a PPT-containing RNA/DNA hybrid reveals potential hydrogenbonding contacts between the ϩ1 RNA base and Arg-448, and between the Ϫ2 RNA base and Gln-475 (35) that might contribute to the observed sequence preferences.…”
Section: Volume 281 • Number 4 • January 27 2006mentioning
confidence: 99%